Kontribusi Metode Hafalan Kitab Jurumiyah terhadap Pemahaman Kitab Kuning Santri di Pondok Pesantren Al Istiqomah Tanjungsari Petanahan Kebumen - Khofifah Khofifah; Robingun Suyud El Syam; Rifqi Aulia Rahman (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
This study aims to analyze the implementation of the memorization method of the Jurumiyah book in improving students’ understanding of the yellow book at Al-Istiqomah Islamic Boarding School, identify supporting and inhibiting factors, and examine its contribution to students’ learning abilities. This research employed a descriptive qualitative field study conducted at Al-Istiqomah Islamic Boarding School in Tanjungsari Village, Petanahan, Kebumen, from December 2025 to February 2026. The research subjects included caregivers, khadimul ma’had, ustadz or ustadzah, and students. Data were collected through interviews, observation, and documentation, then analyzed descriptively. The findings show that the memorization method of the Jurumiyah book is implemented through stages of preparation, memorization deposit, and evaluation. In the memorization process, students not only memorize the text but also understand its meaning and apply nahwu rules in reading the yellow book. Several supporting techniques, such as lalalaran, association, the cantol system, and tikrar, help strengthen students’ memorization. Supporting factors include motivation, discipline, teacher guidance, and a conducive environment, while inhibiting factors include differences in students’ abilities, lack of concentration, and limited learning time. Overall, the method contributes positively to improving students’ ability to read and understand the yellow book.